EFEKTIVITAS LAYANAN INFORMASI KARIR DALAM MENINGKATKAN MINAT MELANJUTKAN STUDI KE SMK PARIWISATA PADA SISWA KELAS IX SMP NEGERI SATAP PANTANGOLEMBA KAB.POSO - Morundu, Deysin; Munir, Abd; Nurwahyuni, Nurwahyuni (Jurnal Konseling dan Psikoedukasi, 2017)
The problem of this research is student’s interest of further study to SMK Pariwisata before and after the implementation of career information service, also whether career information service effective to increase interest of further study to SMK Pariwisata. This research intended todescribe the effectiveness of career information service to increaseinterest of student’s further study . The subjects in this research were 20 students. The data was collected by havinginterest of further study to SMK Pariwisata questionnaire.The data was processed and analyzed in descriptive and inferentially. The result of descriptive analysis showed that before implementation ofcareer information service there were 30% of students had high interest of further study, 55%  of students had low interest of further study, and 15% of students had very low interest of further study. On the other side afterimplementation ofcareer information service there wereenhancement of interest of further study, i.e:20% of students had very high interest of further study, 70% of students had high interest of further study, and 10% of students had low interest of further study. So it can be conluded that career information service was effective to increaseinterest of further study to SMK Pariwisata of students in grade IX SMP Negeri Satap Pantangolemba Kab.Poso.